Validation of Spadella kappae Schmidt-Rhaesa & Vieler, a small benthic chaetognath from Roscoff, France (Chaetognatha) - Schmidt-Rhaesa, Andreas; Vieler, Vera (Zootaxa, 2020)
Schmidt-Rhaesa & Vieler (2018) described a new species of benthic chaetognath, Spadella kappae, collected by meiofaunal sampling near Roscoff, France. Although the description and figures presented by Schmidt-Rhaesa & Vieler (2018) fully characterize the new species, the journal issue in which the description appeared was published online-only, with no print version, and the article in which the new name appeared did not include a ZooBank registration number for the article (LSID), required for validation of new species names in electronic-only publications (ICZN 2012). As a result, the name Spadella kappae Schmidt-Rhaesa & Vieler, 2018, as published in Cahiers de Biologie Marine 59: 257–265, is not available according the International Code of Zoological Nomenclature, hereafter, the Code (ICZN 1999, 2012). Therefore, the present note serves to validate the name Spadella kappae by fulfilling Code conditions for nomenclatural availability. The date and authorship of the specific name, accordingly, are those of this note, not Schmidt-Rhaesa & Vieler (2018).